2003
DOI: 10.1074/jbc.m304494200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathway for Cancer Metastasis to Bone

Abstract: The molecular mechanism leading to the cancer metastasis to bone is poorly understood but yet determines prognosis and therapy. Here, we define a new molecular pathway that may account for the extraordinarily high osteotropism of prostate cancer. By using SPARC (secreted protein, acidic and rich in cysteine)-deficient mice and recombinant SPARC, we demonstrated that SPARC selectively supports the migration of highly metastatic relative to less metastatic prostate cancer cell lines to bone. If prostate cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 30 publications
9
130
0
3
Order By: Relevance
“…Our results from GeneChip analysis and quantitative evaluation of SPARC mRNA expression in 110 CaP patients are consistent with the literature that indicates a role for SPARC, 22,23 and a high expression of SPARC protein 20 , in metastasis. Therefore, we hypothesized that high SPARC expression (likely at protein level as SPARC is functionally linked to metastasis) in primary prostate tumors may predict a higher chance of later metastasis.…”
Section: High Sparc Protein Expression In Cap Is Associated With An Isupporting
confidence: 91%
See 2 more Smart Citations
“…Our results from GeneChip analysis and quantitative evaluation of SPARC mRNA expression in 110 CaP patients are consistent with the literature that indicates a role for SPARC, 22,23 and a high expression of SPARC protein 20 , in metastasis. Therefore, we hypothesized that high SPARC expression (likely at protein level as SPARC is functionally linked to metastasis) in primary prostate tumors may predict a higher chance of later metastasis.…”
Section: High Sparc Protein Expression In Cap Is Associated With An Isupporting
confidence: 91%
“…Of note, there was conservation of NKXH_NKXH_HOX composite regulatory elements in the promoters of the genes in this network suggestive of the biological significance of this gene-expression regulatory mechanism in CaP progression. As SPARC has a role 22,23 and high protein levels 20 in metastasis, we hypothesized that high SPARC expression in primary tumor may predict future metastasis. Indeed, further analysis revealed that high SPARC protein expression in malignant prostate cells at the time of RP is associated with an increased risk of tumor metastasis (see study flow chart in Supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports highlight the role of this molecule as a positive or negative modulator in the pathogenesis of different malignancies (18)(19)(20)(21)(22)(23)(24). We and others have shown that SPARC functions as a tumor suppressor in ovarian cancer (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 89%
“…VEGF is known to exert an autocrine as well as paracrine mitogenic effect on a variety of tumor cells including melanoma, prostate cancer, and ovarian cancer in vivo (22,(35)(36)(37)(38). Our pilot studies indicated that VEGF stimulates the proliferation of ID8 cells in a concentration-dependent manner (data not shown).…”
Section: Sparc Inhibits Vegf-induced Proliferation and Survival Of Ovmentioning
confidence: 99%